YAP and TAZ regulate adherens junction dynamics and endothelial cell distribution during vascular development - Neto, Filipa (2018)
© Copyright Neto et al. This article is distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use and redistribution provided that the original author and source are credited.